Enseignement et évaluation de la prononciation aujourd'hui : l'intelligibilité comme enjeu - Marion Didelot; Isabelle Racine; Françoise Zay; Alexei Prikhodkine (Recherches en didactique des langues et des cultures)
In an increasingly globalised world, new challenges have emerged relating to the evaluation of oral language competence. The phonetic component holds a dominant place here, and this paper constitutes a reflection around two notions, i.e. intelligibility – an upcoming objective of modern pronunciation teaching –, and accented speech, in light of their place and usage in the descriptor of phonological competence in CEFRL (Common European Framework of Reference for Languages). We compare the old and the recently revised version of the descriptor, and although the latter undeniably constitutes an improvement, much work still needs to be done when it comes to pronunciation and the training of teachers and assessors.